If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4u + 38 = -2(u + -1) Reorder the terms: 38 + 4u = -2(u + -1) Reorder the terms: 38 + 4u = -2(-1 + u) 38 + 4u = (-1 * -2 + u * -2) 38 + 4u = (2 + -2u) Solving 38 + 4u = 2 + -2u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '2u' to each side of the equation. 38 + 4u + 2u = 2 + -2u + 2u Combine like terms: 4u + 2u = 6u 38 + 6u = 2 + -2u + 2u Combine like terms: -2u + 2u = 0 38 + 6u = 2 + 0 38 + 6u = 2 Add '-38' to each side of the equation. 38 + -38 + 6u = 2 + -38 Combine like terms: 38 + -38 = 0 0 + 6u = 2 + -38 6u = 2 + -38 Combine like terms: 2 + -38 = -36 6u = -36 Divide each side by '6'. u = -6 Simplifying u = -6
| 24x^4(x+3)+30x^3(x+3)+18x^2(x+3)= | | (2z-5)(1+z)=0 | | A=PI^2+PIrs | | 16x^2-32x+256=238 | | 2(2u-7)=22 | | -41=y/8 | | x^2/3=15 | | 4.4x+0.2=5.3x-4.3 | | 8x+64=20x | | 198*1/18 | | x+23=74 | | X=.75(.5(.5x+5)+5)+5 | | 16x^2-32x+256=0 | | v/2-5v/6=v/12 | | 2/53=-14 | | -24=-12n | | s+5s-45= | | 19x=x+54 | | (1/5)N=252 | | 2x+1=3x+-2 | | 5(x+5)=13 | | T=1/2PV | | 6w^2-w=1 | | (2x^-8/^-2)^-3 | | 3w^2-5w=70 | | 3x/3-x=x/6-3/2 | | 1/5(252) | | y+-1=-2 | | -5x^2+12=57 | | 6x-5.75=-4.25 | | 2a-(a-5)= | | 9-6(4u-1)=u+5 |